Utilizing Cooperative Learning as an Effective Method to Improve Students’ Writing Skills - Mantra, Ida Bagus Nyoman; Maba, Wayan; Widiastuti, Ida Ayu Made Sri (PT. Riset Press International, 2025)
The primary goal of this study is to discover whether the cooperative learning technique may help students enhance their writing skills. This study used a classroom action research approach with two cycles. The relevant data were acquired using research instruments such as monologue performance tests and structured questionnaires. Following the study cycle process, it was determined that cooperative learning was an effective teaching strategy for improving the student's writing skills, particularly in drafting and performing short descriptive monologues. The pre-test, post-test 1, and post-test 2 showed that the students writing skills have improved significantly. In addition, a structured questionnaire revealed a positive reaction to using cooperative learning. It can be stated that cooperative learning can help students enhance their writing skills. This study suggests teachers should employ cooperative learning as much as possible when teaching English.